The Impact of Macroeconomic Uncertainty on Cash Holdings for Non-Financial Firms - Oleksandr Talavera; Neslihan Ozkan; Mustafa Caglayan; Christopher F. Baum (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
This paper investigates the effects of macroeconomic volatility on nonfinancial firms cash holding behavior. Using an augmented cash bufferstock model, we demonstrate that an increase in macroeconomic volatility will cause the crosssectional distribution of firms cashtoasset ratios to narrow. We test this prediction on a panel of nonfinancial firms drawn from the annual COMPUSTAT database covering the period 19572000, and find that as macroeconomic uncertainty increases, firms behave more homogeneously. Our results are shown to be robust to the inclusion of the levels of several macroeconomic factors.
Keywords: 330; Cash holdings; macroeconomic uncertainty; time series; ARCH; nonfinancial Firms.; Liquide Mittel; Betriebliche Liquidität; Makroökonomischer Einfluss; Volatilität; Konjunktur; Schätzung; Vereinigte Staaten